PERUBAHAN BUYING BEHAVIOR DARI PERSPEKTIF BRAND, PRICE AND VALUE PERCEPTION, MARKETING RESPONSE DAN CONSUMER ENGAGEMENT" KASUS PADA KONSUMEN ONLINE SHOP DI SURABAYA - Siti Aminah; Hwihanus (Jurnal Ekonomi dan Bisnis, 2024)
The growth of e-commerce is also driven by the adoption of innovative digital technologies and platforms. Many e-commerce companies, both local and international, have invested in technology that makes transactions easier for users, such as secure payment systems, fast delivery, and a more personalized shopping experience. In addition, financial inclusion and accelerated penetration of digital payment methods have facilitated online transaction processes, providing convenience for consumers which in turn drives the growth of the e-commerce sector in Indonesia. All these factors together have created a fertile landscape for the development of e- commerce in Indonesia, becoming one of the largest and most promising e-commerce markets in the Southeast Asia region. This research aims to analyze the following things: 1). To analyze changes in purchasing behavior among online shop consumers in Surabaya from the perspective of brand, price and value perception, marketing response, and consumer engagement. 2). To understand the relationship between these factors in the context of changing purchasing behavior. 3). To identify the most significant factors influencing changes in purchasing behavior of online shop consumers in Surabaya. This research uses primary data by distributing questionnaires electronically on the website https//www. panel.kuisioner.com. The sampling technique uses non-probability sampling, namely convenience sampling, where with this sampling technique, researchers take samples according to their needs and of course those that are related to the variables being studied. Meanwhile, in collecting data, observation, structured interviews, questionnaires and literature study were used. Once the data is obtained it will be analyzed using quantitative analysis with the help of the SPSS Version 26 application. After data processing, it can be concluded that all the variables studied (Brand, Price and Perceived Value, Marketing Response, Consumer Engagement) have a significant influence on Buying Behavior. This confirms the importance of understanding in depth consumer preferences and needs through further research. will provide better insight regarding their preferences in the context of the online shop market in Surabaya and emphasizes an in-depth understanding of the variables that influence purchasing behavior in the online shop market can help companies direct their marketing strategies more effectively, optimize interactions with consumers, and increase sales performance and consumer loyalty